Ilmu Pengetahuan Sosial Sebagai Transmisi Kewarganegaraan - Alsi Ratu Balqis; Emilia Susanti; Elsa Ramayeni; Maisya Putri; Bahria Bahria; Tsaniyah Andini; Zumri Syahferi Harahap (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to analyze the role of Social Studies (IPS) in transmitting citizenship values to high school students. In the context of globalization and rapid social changes, citizenship education through IPS is considered essential for strengthening national identity and instilling democratic values and social responsibility. The research method used is a descriptive qualitative approach, with data collection techniques including semi-structured interviews, non-participant observation, and document analysis. The research sample consists of 10 IPS teachers and 20 high school students in city X, selected through purposive sampling. The collected data were analyzed through data reduction, data presentation in the form of descriptive narratives, tables, or diagrams, and conclusion drawing with data triangulation. The results show that 78% of students who study IPS have a better understanding of their rights and obligations as citizens compared to students who do not study IPS. Interviewed teachers stated that IPS not only teaches history and geography but also the values of democracy, tolerance, and social justice. This study confirms that IPS is a crucial tool in building knowledgeable and active citizens. These findings support the citizenship education theories of John Dewey, Albert Bandura, and the constructivist theories of Jean Piaget and Lev Vygotsky. Overall, IPS is effective in shaping the character and citizenship identity of students, preparing them to become positive agents of change in society